PENINGKATAN PENDAPATAN ASLI DAERAH KOTA BANDUNG: STUDI PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TAHUN 2009-2013 - Asep Mulyana (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Abstract: The purpose of this study was to determine the effect of the development of Regional Taxes and Regional Retribution on increasing Regional Original Revenue (PAD). The research method used is quantitative descriptive analysis. that is, the presentation of data in the form of numbers. This research consists of two independent variables, namely Regional Taxes and Regional Retribution. The classic assumption test used is normality test, multicollinearity autocorrelation test, and heteroscedasticity test. The data analysis model used is multiple linear regression analysis. The results showed the highest growth rate in 2011 reached 45.21% while the realization of PAD revenue which showed the lowest growth rate was in 2010 which was only 15.42%. The average growth of PAD revenue in Bandung in 2009-2013 was 22.19%, while in descriptive statistics it was Rp.812.20 billion. The test results show that the Regional Tax has a significant effect while the Regional Retribution has no significant effect on the Bandung City PAD. Simultaneously, Bandung City PAD is 100% influenced by regional taxes and retribution. Keywords: Regional Taxes, Regional Retribution, Regional Income